INDONESIAN CRIMINAL POLICY AGAINST FRAUD IN THE BANKING FIELD - Febriansyah, Artha; Saputra, Ishandi; Syafrianto, Arief (Sriwijaya Crimen and Legal Studies, 2023)
Various fraud cases in the banking sector have recently tarnished the meaning of banking as a pillar of national economic development. Regulations regarding handling fraud have also been regulated in several regulations, such as the Criminal Code, the Banking Law, and other special regulations. So, an institution that is expected to restore stability to the national economy was formed, known as the Financial Services Authority. OJK and Bank Indonesia can coordinate and cooperate in joint supervision of financial services activities in the banking sector. This research looks at Indonesian criminal policies in enforcing and handling crimes in the banking sector, especially regarding fraud. By looking at the institutional relationship between Bank Indonesia and the Financial Services Authority, it is hoped that they can coordinate to reduce the number of frauds in Indonesia. The method used is documentary research, where researchers see and analyze problems using selected document data. From the results of this research, it was found that banking crimes committed by bank insiders (crimes against the bank) need special attention. "Insider" crimes are closely related to the domination of policy and administration by one or several people and weak supervision by internal and external supervisors (regulators). In addition, various applicable regulations often cause banks to take excessive risks, which causes a decrease in the level of internal supervision, so bank failures caused by fraud by insiders become higher.